Pelatihan Aplikasi Power Point sebagai Media Pembelajaran Jarak Jauh di Pondok Pesantren Assubkiyah - Mohamad Tohir; Aisyi Syafikarani; Adya Mulya Prajana (Charity : Jurnal Pengabdian Masyarakat, 2021)
This training is an activity for teachers and students of the Visual Communication Design Study Program - Creative Industry Faculty of Telkom University in helping to develop skills related to the profession of teachers at the Assubkiyah Islamic Boarding School with the theme "Training on Power Point Application as a Distance Learning Media at the Assubkiyah Islamic Boarding School". This activity aims to: 1) Provide scientific contributions, especially the Visual Communication Design study program for the general public; 2) Developing skills related to the profession of teachers / teaching staff at the Assubkiyah Islamic Boarding School; 3) Provide provision of skills; and 4) Provide opportunities for teachers and administrators of Islamic boarding schools to gain / increase knowledge that is not taught in the school environment. It is hoped that after this program takes place, the teachers and administrators of the Assubkiyah Islamic Boarding School can add to their skills so that teaching and learning activities can take place better.